Media dalam Perjanjian Lama dan Relevansinya bagi Pembelajaran PAK PAUD pada Masa Kini - Ambarita, Ida Sortauly (Sekolah Tinggi Teologi Borneo, 2022)
Abstract: The proper learning of Christian religious education for a child starts from the golden age,namely the age of 0 – 6 years, when the whole potential experiences a period of great and fast growthand development sensitivity. From an early age, children are introduced to Bible teaching andknowledge of the Lord Jesus every day and continuously so that the Word of God takes root andbears fruit in the children. Therefore, Christian Religious Education is expected to carry out its dutiesseriously in accordance with the objectives of education and learning, namely to form and create ageneration that has noble character, is responsible and has the character of Christ. In learningChristian religious education at PAUD today, a useful media is needed as a tool to convey messagesfrom educators to students, especially early childhood education. With the media, it is hoped that theobjectives of learning Christian religious education will be achieved. This study aims to explore themedia in the Old Testament and find their relevance for learning Christian religious education earlychildhood education today. The writing of this article uses descriptive qualitative research methodswith literature investigations through books, journals and articles about the media in the OldTestament and their relevance for learning Christian religious education. Early childhood educationtoday. The conclusion is the relevance of the Old Testament media with learning Christian religiouseducation early childhood education today.Keywords: Old Testament media, Christian religious education, early childhood education mediaAbstrak: Pembelajaran pendidikan Agama Kristen yang tepat bagi seorang anak dimulai dari masaemas yaitu usia 0-6 tahun yaitu masa di mana keseluruhan potensi mengalami masa kepekaantumbuh kembang yang hebat dan cepat. Sejak usia dini anak – anak diperkenalkan pada pengajaranAlkitab maupun pengenalan akan Tuhan Yesus setiap hari dan terus menerus sehingga FirmanTuhan berakar dan berbuah di dalam diri anak-anak. Oleh karenanya Pendidikan Agama Kristendiharapkan agar melaksanakan tugasnya dengan sungguh-sungguh sesuai dengan tujuan pendidikandan pembelajaran yakni membentuk dan menciptakan generasi yang berakhlak mulia, bertanggungjawab dan memiliki karakter Kristus. Dalam pembelajaran pendidikan agama Kristen padaPaud masa kini diperlukan suatu media yang berguna sebagai alat menyampaikan pesan dari pendidikke peserta didik khususnya pendidikan anak usia dini. Dengan adanya media diharapkantujuan dari pembelajaran pendidikan agama Kristen akan tercapai. Tujuan dari penelitian ini adalahuntuk menggali media dalam Perjanjian Lama dan menemukan relevansinya bagi pembelajaranpendidikan agama Kristen Pendidikan anak usia dini masa kini. Penulisan artikel ini menggunakanmetode penelitian kualitatif deskriptif dengan penyelidikan literature melalui buku, jurnal danartikel mengenai media dalam Perjanjian lama dan relevansinya bagi pembelajaran pendidikanagama Kristen Pendidikan anak usia dini masa kini. Adapun hasil kesimpulan adalah adanyarelevansi media Perjanjian Lama dengan pembelajaran pendidikan agama Kristen Pendidikan anakusia dini masa kini.Kata kunci: media Perjanjian Lama, Pendidikan agama Kristen, Paud masa kini